Nitrate Content in Root, Tuber, and Leafy Vegetables in Wet Markets in Hanoi: A Health Risk Assessment - Thi Phuong Mai, Nguyen; Thi Diu, Dinh; Thi Thao Vy, Truong; Thi Phuong thao, Nguyen; Huong Thao, Trinh; Thai Son, Phung (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1SDO - 10.25073/2588-1094/vnuees.5207, 2024)
Nitrate (NO 3 – ) is a natural compound occurring in foods, especially plant produces, and are also used as additives in industrially processed foods. This study aims to assessing the nitrate contents and health risk in root, tuber, and leafy vegetables in several wet markets in Hanoi. The results showed that the mean nitrate concentration in root and tuber vegetables, herbs and leafy vegetables ranged from 59 to 1118 mg/kg, from 580 to 1204 mg/kg, and from 122 to 3600 mg/kg, respectively. NO 3 – content in some vegetables at the local market and supermarket were from 1.2 (green beans) to 2.4 times (cucumber) and from 1.4 (long wax gourd) to 3.7 times (radish) higher than World Health Organization (WHO) standards, respectively. The risk assessment of the Estimated Daily Intake (EDI) results shows that the vegetable samples was 23% and 61% in the acceptable value according to WHO for children and adults, respectively. The Hazard Index (HI) shows that, the HI values of nitrate for all samples except for celery were < 1, indicating that health risks for adults associated with nitrate exposure were not significant. On the contrary, 70% of vegetable samples had HI > 1, suggesting adverse effects on children health that consume these vegetables.